Differentials of the immunization program in rural Bangladesh and the issue of userfee - Kamal, Firoz Mahboob; Hadi, Abdullahel; Chowdhury, A Mushtaque R. (BRAC Research and Evaluation Division (RED), 2020)
This study investigated some aspects of the sustainability of the immunization program by exploring the association between immunization coverage and price affordability with some selected socioeconomic variables in rural Bangladesh. It was conducted in 75 villages in I 0 areas of five administrative districts. Eligible interviewees were 1145 resident mothers having a child of age 12 to 23 months. Both paternal and maternal education were found to have a significant influence on immunization. There was no significant association between immunization coverage and child's sex, household's cultivable land, labor sale and NGO involvement. Exposure to media like radio increases predictability of immunization by about two folds. Most people wish to pay none or minimal userfee, therefore restrict the financial sustainability of the program on its own. An increase in parental education enhances the willingness to pay userfees.